Statistical Analysis of APXS‐Derived Chemistry of the Clay‐Bearing Glen Torridon Region and Mount Sharp Group, Gale Crater, Mars. Issue 9 (19th September 2022) - O'Connell‐Cooper, C. D.; Thompson, L. M.; Spray, J. G.; Berger, J. A.; Gellert, R.; McCraig, M.; VanBommel, S. J.; Yen, A.
Abstract: The Glen Torridon stratigraphic sequence marks the transition from the low energy lacustrine‐dominated Murray formation (Mf) (Jura member: Jm) to the more diverse Carolyn Shoemaker formation (CSf) (Knockfarril Hill member: Knockfarril Hill; Glasgow member: Glasgow). This transition defines a change in depositional setting. Alpha Particle X‐ray Spectrometer (APXS) results and statistical analysis reveal that the bulk primary geochemistry of Mf targets are broadly in family with CSf targets, but with subtle compositional and diagenetic trends with increasing elevation. APXS results reveal significant compositional differences between Jura_GT and the stratigraphically equivalent Jura on Vera Rubin ridge (Jura_VRR). The data define two geochemical facies (high‐K or high‐Mg), with a strong bimodal grain distribution in Jura_GT and Knockfarril Hill. The contact between Knockfarril Hill and Glasgow is marked by abrupt sedimentological changes but a similar composition for both. Away from the contact, the Knockfarril Hill and Glasgow plot discretely, suggesting a zone of common alteration at the transition and/or a gradual transition in provenance with increasing elevation in the Glasgow member. APXS results point to a complex history of diagenesis within Glen Torridon, with increasing diagenesis close to the Basal Siccar Point unconformity on the Greenheugh pediment, and with proximity to the beginning of the clay sulfate transition. Elemental mobility is evident in localized enrichments or depletions in Ca, S, Mn, P, Zn, Ni. The highly altered Hutton interval, in contact with the unconformity on Tower butte, is also identified on Western Butte, indicating that the "interval" was once laterally extensive. Plain Language Summary: The Mars Science Laboratory Curiosity rover has traversed the Glen Torridon locale in Gale crater, Mars. The rover has provided evidence in the rocks of a change from a lake setting to a river setting, with increasing elevation through the rock record. Geochemical results from the Alpha Particle X‐ray Spectrometer (APXS) confirm a slow change in composition over time as the sediments that formed the rock were laid down. Fluids percolated through the sediments, altering the composition, with localized enrichments of calcium, sulfur, manganese, phosphorus, sodium, zinc, nickel, which are now present as veins, and small (typically <0.3 cm; more rarely, 0.5–2 cm) rectangular nodules and concentrations. Key Points: Alpha Particle X‐ray Spectrometer data for Glen Torridon, Gale crater documents subtle compositional changes Multiple episodes of alteration and diagenesis identified Compositional similarities between Glen Torridon members confirms the highly localized nature of the Vera Rubin ridge alteration